Towards the low carbon cities, looking at the world and scenarios for municipalities in Vietnam - Lam, Nguyen Tung (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2018)
Vietnam has entered into the Paris Agreement with a view to reducing greenhouse gas emissions, towards sustainable development and in line with the national green growth strategy. Urban area play an important role in the economy, and the urbanization process is predicted to continue to increase in the future. Planning for urban development in the direction of reducing greenhouse gas emissions is therefore important in efforts to achieve the country’s goal of reducing greenhouse gas emissions. This article will introduce the experiences of some Asian countries in low-carbon policy planning in urban areas and test the development of low-carbon scenarios for some cities in Vietnam. On this basis, the author will provide some initial recommendations for mainstreaming greenhouse gas reduction targets in urban development policy with priorities for promoting climate change technology. Code: 17042102